Infodemic and media literacy in the face of the risks of automated disinformation in digital environments - Guevara Chávez, Jorge Luis; Almeida Macias, Mercedes Roxana (Scripta Mundi, 2025)
In today’s digital environment, one of the most pressing threats to information quality and public trust is the relentless surge of automated content, especially bots, deepfakes and biased algorithms. Driven by this challenge, the present study sets out to identify and synthesize the most effective media literacy strategies deployed between 2019 and 2025 to neutralize these specific risks. Following the PRISMA-ScR framework, a comprehensive scoping review was carried out in which 42 key studies were rigorously selected and examined through both qualitative and quantitative lenses, including the calculation of an aggregated effect size (Hedges’ g). The analysis shows that a combined approach—training in critical thinking, use of automated verification tools, and basic algorithmic education—delivers the strongest results (g≈0.71), far outperforming any of these tactics alone. The significance of an integrated media literacy paradigm that really increases users’ resistance to automated disinformation is shown by these findings. Lastly, the study offers specific suggestions for incorporating these insights into educational curricula, especially in Latin America, so that people can successfully and unflinchingly traverse the complicated information environment of today.
Keywords: infodemic; media literacy; automated misinformation; digital media; algorithmic bias; fact checking